Outplacement Adequacy and Benefits: The Mediating Role of Overall Justice. Issue 3 (September 2016) - Marzucco, Laurence; Hansez, Isabelle
Abstract : Despite a rapid growth and an ongoing need for outplacement services, little is known about the perceived adequacy and benefits of these services for the redundant employees using them. The authors surveyed 360 Belgian redundant employees (i.e., clients) who were using outplacement services provided by a public employment agency. Results indicated that an outplacement experience that is perceived as adequate by clients fosters their overall impressions of justice toward the dismissing organization. Perceived outplacement adequacy, in turn, led to benefits for the redundant employees—namely, a reduction of negative emotions and an enhancement of their perceived well‐being, future perspectives, and job‐seeking activities—thus confirming the mediating role of overall justice.